FAKTOR-FAKTOR YANG MEMPENGARUHI KECELAKAAN KERJA PADA PROSES DIE CASTING DI PT. X CIKARANG BARAT KABUPATEN BEKASI JAWA BARAT - Nurbaiti Fadhilah; Suryanto Suryanto; Nur Ulfah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT Accidents in workplace could cause a lot of loss and death. Based on the data from accident reports of PT. X in 2009, there were 30 cases of working accidents 35 cases occurred in 2010 and 42 cases occurred in 2011. The occurrence of occupational accidents had increased during the last 3 years from 2009 to 2011. This study aimed to determine the factors that in fluence occupational accidents on Die Casting process at PT. X on West Cikarangin Bekasi,West Java. The type of this research was an observational study using crosssectional approach. Samples ofthis research were 71 workers on die casting process. Data Analyses used univariate, bivariate (Chi-Square test) and multivariate (Multiple Logistic Regression) Analyses. Based on the research result, there was nonsignificant relationship between age (p = 0.239), knowledge (p = 0.014), work duration (p = 0.629), work procedure (p = 0.350), noise (p = 0.512), and lighting (p = 0.259) with the events of occupational accidents in the PT X. Meanwhile, there were asignificant relationship between work shift (p =0.009) and the use of Personal Protective Equipment (PPE) (p = 0.014) with the incidence of occupational accidents in the PT X. The results of multiple logistic regression test showed that there were significant effect on the use of PPE with the occurrence of occupational accidents, that wasthe use of PPE (p = 0.022). It is advisable to the company to provide supervision and give firm sanction to the labors who do not use PPE during working. Keywords : Occupational accidents, Influence factor Kesmasindo, Volume 6(2) Juli 2013, Hal 135-142